Radial Peripapillary Capillary Network in Patients with Retinitis Pigmentosa: An Optical Coherence Tomography Angiography Study - Mastropasqua, Rodolfo; Borrelli, Enrico; Agnifili, Luca; Toto, Lisa; Di Antonio, Luca; Senatore, Alfonso; Palmieri, Michele; D’Uffizi, Alessandro; Carpineto, Paolo (Frontiers in Neurology, 2017)
Purpose: To investigate radial peripapillary capillary (RPC) network in patients affected by retinitis pigmentosa (RP). Methods: Eleven patients (22 eyes) with previous diagnosis of RP and 16 age-matched healthy subjects (16 eyes) were enrolled. The diagnosis of RP was made based on both clinical features and electrophysiological examination. All patients underwent a complete ophthalmologic examination, including optical coherence tomography angiography (OCTA), and visual field (VF). The primary outcomes were the RPC vessel density in the peripapillary and disc areas; the secondary outcomes were the peripapillary retinal nerve fiber layer (RNFL) thickness, and the mean defect (MD) at VF. Results: A total of 19 eyes of 11 RP patients (5 male, 6 female) and 16 eyes of 16 healthy subjects (10 male, 6 female) were included for the analysis. RPC vessel density in the disc area was 46.5±7.1% in the RP group and 45.4±10.6% in the control group (p=0.754). RPC vessel density in the peripapillary area was significantly reduced in the RP group after the comparison with the control group (52.5±5.0% and 57.2±5.1%, respectively, p=0.011). RNFL thickness was 85.9±20.4 μm in the RP group and 104.0±6.4 μm in the control group (p=0.002). RPC vessel density was significantly correlated with RNFL thickness values in RP patients, both in the disc and in the peripapillary area (Rho=0.599 and p=0.007 in the disc area, Rho=0.665 and p=0.002 in the peripapillary area, respectively). Conclusions: We showed that density of RPC is reduced in these patients in the peripapillary area. Moreover, the RPC vessel density correlates with the RNFL thickness.